The Gudali of Nigeria - Review - Ngere, L.O. (Food and Agriculture Organization of the United Nations, 1985)
Paper presented at the expert committee meeting on animal genetic resources in Africa, 1983. Reviews the Gudali of Nigeria. Describes the general features of the breed, natural habitat, numbers and systems of husbandry. Detailed discussions on breed characteristics including external feature, productivity, milk yield, beef production, reproductive performance, disease, mortality and adaptability included.